First flush phenomenon study of storm runoff from a maize cultivated area - Mansur, Rusnam; Mohd Soom, Mohd Amin; Idris, Azni; Lee, Teang Shui (2005)
Various studies conducted worldwide could not ascertain the existence of the first flush in every drainage outlet, during every storm event and for each pollutant. Hence there is a need to study the first flush phenomenon of runoff from an agricultural area. Rainfall in three seasons of maize cultivation was monitored. Twenty storm events of various intensities and durations were monitored in crop season I, nineteen in crop season II and eight in crop season III. Six parameters were monitored for the first flush study. First flush effect for most of the parameters was weak and closed to uniform for every storm event. Although it was minor, total suspended solids (TSS) exhibited first flush during all storm events. As such, first flush separation would not be an effective criterion for diffuse or nonpoint source pollution control in the study area. Based on the rainfall analysis it was recommended that to avoid the ambiguity pertaining to first flush phenomenon and to simplify the criterion for designing the nonpoint source pollution control structures, capture and treatment of first 30 mm runoff would be a good start for Malaysia.